The Influence of the Flipped Classroom Model on Learning Biographical Text Writing Skills: - Sri Revalina; Farel Olva Zuve; Ridha Hasnul Ulya; Tressyalina (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The flipped classroom model is a pedagogical approach that reverses traditional teaching by delivering instruction—often online—outside of class, while moving homework and active learning, such as discussions and collaborative projects, into the classroom. This student-centered method allows learners to study at their own pace, improves engagement, and promotes deeper. This study aims to determine the effect of the use of the flipped classroom learning model on the writing skills of biographical texts of class X students of SMA Negeri 5 Payakumbuh. This type of research is an experiment with the Quasi Experimental Design method. The research design used is Pretest-posttest Control Group Design. The population in this study were 150 class X students of SMA Negeri 5 Payakumbuh registered in the 2025/2026 academic year. The research sample used a purposive sampling technique, namely class X.E 4 experimental class totaling 38 students taught using the flipped classroom model and class X.E 2 control class totaling 37 students taught using project-based learning. The research instrument was a performance test of writing biographical texts. Data were analyzed using parametric inferential statistics, namely the independent sample t-test using SPSS. The results showed: 1) the skills of writing biographical texts taught using project-based learning in the control group only produced a mean of 11.27 which is equivalent to a standard score of 56.35 percent which is included in the low category; 2) the skill of writing biographical texts taught using the flipped classroom model in the treatment group produced a mean of 14.05 which is equivalent to a standard score of 70.25 percent which is included in the moderate category; 3) the flipped classroom model has a significant effect on learning the skill of writing biographical texts in class X of SMA Negeri 5 Payakumbuh compared to project-based learning.